Implementation in monitoring of an UiTM building by using [GNSS] & total station to ensure the safety of future geomatic laboratory / Farah Atiqah Kamil - Kamil, Farah Atiqah (2019)
Deformation monitoring is method to identify the safety of engineering structures. It is very important because of every year new engineering structure has been built. The purpose of this study is to investigate the status of the existing building. The area of study is take place in UiTM Perlis at Al-Farabi 3 Block B. Basically, monitoring can be done by conventional geodetic method which by using Total Station. Besides that, GNSS technology also be apply during this monitoring is perform. GNSS capable to offer three-dimensional results compare conventional. Both are need to establish control points to ensure the measurement is verify with reference points. Plus, establishing target points are also needed for conventional observation made by Total Station. After manage to observe both techniques, the results achieved and can be compare to identify the differences for both results. Therefore, result of redundant readings of observation from conventional and modem method are manage to conclude that whether the building is safe to be occupy.